Non-invasive Auricular Vagus Nerve Stimulation as a Potential Treatment for Covid19-Originated Acute Respiratory Distress Syndrome - Kaniusas, Eugenijus; Szeles, Jozsef C.; Kampusch, Stefan; Alfageme-Lopez, Nuria; Yucuma-Conde, Daniela; Li, Xie; Mayol, Julio; Neumayer, Christoph; Papa, Michele; Panetsos, Fivos (Frontiers in Physiology, 2020)
Background: Covid-19 is an infectious disease caused by an invasion of the alveolar epithelial cells by coronavirus 19. The most severe outcome of the disease is the Acute Respiratory Distress Syndrome (ARDS) combined with hypoxemia and cardiovascular damage. ARDS and co-morbidities are associated with inflammatory cytokine storms, sympathetic hyperactivity, and respiratory disfunction. Hypothesis: In the present paper, we present and justify a novel potential treatment for Covid19-originated ARDS and associated co-morbidities, based on the non-invasive stimulation of the auricular branch of the vagus nerve. Methods: Auricular vagus nerve stimulation activates the parasympathetic system including anti-inflammatory pathways (the cholinergic anti-inflammatory pathway and the hypothalamic pituitary adrenal axis) while regulating the abnormal sympatho-vagal balance and improving respiratory control. Results: Along the paper (1) we expose the role of the parasympathetic system and the vagus nerve in the control of inflammatory processes (2) we formulate our physiological and methodological hypotheses (3) we provide a large body of clinical and preclinical data that support the favorable effects of auricular vagus nerve stimulation in inflammation, sympatho-vagal balance as well as in respiratory and cardiac ailments, and (4) we list the (few) possible collateral effects of the treatment. Finally, we discuss auricular vagus nerve stimulation protective potential, especially in the elderly and co-morbid population with already reduced parasympathetic response. Conclusions: Auricular vagus nerve stimulation is a safe clinical procedure and it could be either an effective treatment for ARDS originated by Covid-19 and similar viruses or a supplementary treatment to actual ARDS therapeutic approaches.